2018
DOI: 10.1371/journal.pone.0205001
|View full text |Cite
|
Sign up to set email alerts
|

Estimating under-observation and the full size of the 2016 Zika epidemic in Rio de Janeiro

Abstract: The 2015-16 Zika epidemic spread quickly from north to south in Brazil. Two striking features were the much higher incidence in young adult women due to sexual transmission, and the serious congenital malformations and miscarriages associated to Zika infection in pregnant women. In this paper we use case reporting data along with live-birth records to reconstruct the full size of the epidemic through a Bayesian probabilistic graph model representing the Zika transmission probabilities of observation (case repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…These differences might be owing to sex hormone differences. The gender statistics of patients with ZIKV reveal that the proportion of female patients is higher than that of male patients ( Bastos and Coelho, 2018 ). The two possible explanations are as follows: One is that ZIKV can be sexually transmitted from male to female, resulting in an increase in the number of female patients.…”
Section: Discussionmentioning
confidence: 99%
“…These differences might be owing to sex hormone differences. The gender statistics of patients with ZIKV reveal that the proportion of female patients is higher than that of male patients ( Bastos and Coelho, 2018 ). The two possible explanations are as follows: One is that ZIKV can be sexually transmitted from male to female, resulting in an increase in the number of female patients.…”
Section: Discussionmentioning
confidence: 99%
“…And the reason for its occurrence is likely to be caused by differences in sex hormones. Through the gender statistics of ZIKV patients, it was found that the female infection is more than the male [37]. Now, there are two possible explanations for this.…”
Section: Discussionmentioning
confidence: 99%
“…Included studies were likely subject to selection bias, with one‐fifth restricted to symptomatic mothers and one‐third to foetuses and infants with Zika‐related abnormalities, suggesting significant numbers of Zika‐affected pregnancies may have been missed. If foetal deaths are more common in restricted populations, our foetal death risks may have been overestimated, but if the risk of death is higher with first‐trimester infection when under‐ascertainment of Zika infection is more likely, then foetal death risks may instead have been underestimated [43]. The unreported outcomes in more than half of all Zika‐affected pregnancies could also cause selection bias, if differential across restriction status.…”
Section: Discussionmentioning
confidence: 99%